2009
DOI: 10.1097/eja.0b013e32833244c8
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde autologous priming of the cardiopulmonary bypass circuit reduces blood transfusion in small adults: a prospective, randomized trial

Abstract: RAP resulted in a significant decrease in intraoperative haemodilution and conserved the use of blood. This technique should be considered for patients with a small body surface area (<1.5 m) undergoing open heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 16 publications
1
43
0
1
Order By: Relevance
“…Although recent isolated studies confirm the benefits of recent RAP [13], at least two studies in meta-analysis are not favorable [14,15]. These results suggest that overall.…”
Section: Discussionsupporting
confidence: 64%
“…Although recent isolated studies confirm the benefits of recent RAP [13], at least two studies in meta-analysis are not favorable [14,15]. These results suggest that overall.…”
Section: Discussionsupporting
confidence: 64%
“…7 In a prospective, randomized trial, Hou et al also demonstrated a significant decrease in the intraoperative use of blood, particularly in patients with a small body surface area (<1.5m 2 ). 8 In this study, they included patients with a body surface area <1.5m 2 and excluded those with a preoperative haematocrit <33% and/or an estimated cardiopulmonary bypass time of more than 90 minutes. The total RAP volume in these studies was not expressed as a proportion of the total estimated circulating volume or bodyweight of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Partially priming of the cardiopulmonary bypass circuit with the patient's own blood at the initiation of bypass, known as retrograde autologous priming (RAP), has been shown to reduce the deleterious effects of haemodilution. [1][2][3][4][5][6][7][8][9][10] RAP is thought to maintain COP, reduce pulmonary oedema and haemodilution upon the onset of CPB, which has been shown to improve clinical outcomes, reduce ventilator times in the postoperative period and may reduce the requirements for autologous blood transfusion after cardiac surgery. [6][7][8][9][10][11][12][13] A significant trend towards reduced postoperative weight gain (an indicator of third-space fluid sequestration) demonstrated in the RAP group of patients has possibly contributed to reduced length of postoperative hospital stay after cardiac operations.…”
Section: Introductionmentioning
confidence: 99%
“…Further we routinely utilize RAP, a method of passive exchange of autogolous blood into the arterial and venous lines prior to the initiation of cardiopulmonary bypass which reduces the priming volume, to minimize hemodilution. RAP has been demonstrated in a recent meta‐analysis of six trials to reduce intraoperative transfusions by 64% and total hospital transfusions by 74% 23,24 . The technique of intraoperative autogolous blood donation, removal of 1 L of blood prior to cardiopulmonary bypass to be stored and given back at the end of the case, has been described by some groups and found to be effective 25,26 .…”
Section: Discussionmentioning
confidence: 99%